2019
DOI: 10.1016/j.jval.2019.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Health Technology Assessment Challenges in Oncology: 20 Years of Value in Health

Abstract: Background: Oncology treatments have changed from chemotherapies to targeted therapies and more recently immunooncology. This has posed special challenges in the field of health technology assessment (HTA): capturing quality of life (QOL) associated with toxicity due to chemotherapy, crossover upon progression in targeted therapy trials, and survival extrapolation for immuno-oncology drugs.Objectives: To showcase 20 years of Value in Health (ViH) publications in oncology.Methods: A review was undertaken of onc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 85 publications
(93 reference statements)
0
24
0
Order By: Relevance
“…Maes et al propose two possible solutions to comply with the ESA: the payer pays for the service of the treatment delivering long-term health outcomes or the payer pays for data services as a delivered data package per year instead of paying for a single treatment administration (Maes et al, 2019). Furthermore, healthcare systems wishing to implement spread payments may face national legal barriers which may require adjustment of country-specific regulations (Carlson et al, 2009;Carlson et al, 2011;Espin et al, 2011;Ferrario and Kanavos, 2013;Tuna et al, 2014;Kleinke and McGee, 2015;Barlas, 2016b;Proach et al, 2016;Montazerhodjat et al, 2016;Kanavos et al, 2017;Nazareth et al, 2017;NEHI, 2017;PWC Health Research Institute, 2017;Spark et al, 2017;Goncalves et al, 2018;Salzman et al, 2018;Infante et al, 2019;Lorente et al, 2019;Mahendraratnam et al, 2019). For instance, the current legislation in Spain only allows long-term spending for certain investments which excludes medicines and Sweden does not allow payments for more than three years for non-investment consumables (that are not purchased to deliver financial return) (Alliance for Regenerative Medicine, 2019).…”
Section: Barriers and Potential Opportunities For Implementing Spreadmentioning
confidence: 99%
See 1 more Smart Citation
“…Maes et al propose two possible solutions to comply with the ESA: the payer pays for the service of the treatment delivering long-term health outcomes or the payer pays for data services as a delivered data package per year instead of paying for a single treatment administration (Maes et al, 2019). Furthermore, healthcare systems wishing to implement spread payments may face national legal barriers which may require adjustment of country-specific regulations (Carlson et al, 2009;Carlson et al, 2011;Espin et al, 2011;Ferrario and Kanavos, 2013;Tuna et al, 2014;Kleinke and McGee, 2015;Barlas, 2016b;Proach et al, 2016;Montazerhodjat et al, 2016;Kanavos et al, 2017;Nazareth et al, 2017;NEHI, 2017;PWC Health Research Institute, 2017;Spark et al, 2017;Goncalves et al, 2018;Salzman et al, 2018;Infante et al, 2019;Lorente et al, 2019;Mahendraratnam et al, 2019). For instance, the current legislation in Spain only allows long-term spending for certain investments which excludes medicines and Sweden does not allow payments for more than three years for non-investment consumables (that are not purchased to deliver financial return) (Alliance for Regenerative Medicine, 2019).…”
Section: Barriers and Potential Opportunities For Implementing Spreadmentioning
confidence: 99%
“…These conditions could either be a pre-agreed adjustment of the payment in expectation of competition, as proposed by Towse et al investigating the implications of paying for one-shot cures vs. repeat administrations. Contrarily, Schaffer et al propose the addition of re-opener clauses that foresee provisions for payment adjustment whereas an evaluation of Belgian MEAs suggested the complete termination of the agreement when exclusivity rights expire or a competitive product enters the market (Kanavos et al, 2017;Nazareth et al, 2017;AMCP, 2019;Infante et al, 2019).…”
Section: Barriers and Potential Opportunities For Implementing Spreadmentioning
confidence: 99%
“…Choice of extrapolation of survival data is a common source of uncertainty in cost‐effectiveness assessments of ICI drugs 86 . For example, in guidance document TA519 when considering pembrolizumab, NICE found that using the Gompertz curve for extrapolation assumed that no patient could reside in the postprogressive health state after year 6 17 .…”
Section: Resultsmentioning
confidence: 99%
“…21 Moreover, there seems to be a tendency for payers to be to prepared to enter into 'coverage with evidence' development schemes or risk share agreements. 4,22 This is typically done in order to acquire further data to support the evidence for the incremental costeffectiveness ratio. Unfortunately, while these schemes and agreements offer a solution to early funding as reimbursement is granted even though evidence such as mature survival data is not yet available, the risks are often not well-understood.…”
Section: Risk Share Agreementsmentioning
confidence: 99%
“…For example, the advent of immuno-oncology agents, which have unique biological mechanisms of action and clinical effects, has necessitated new approaches to economic evaluation, especially with regards to extrapolating and translating data beyond the pivotal clinical trials. 4 In countries without mandatory health economic modelling, like South Korea and Taiwan, the utility of early modelling is less clear. However, this strategy can still be used to characterise both the clinical and economic environments within which the new health technology will be assessed for reimbursement.…”
Section: Introductionmentioning
confidence: 99%